آداب الشيخ والمريد الواردة في الرسائل والمؤلفات الصوفية في الفترة الزمنية الممتدة من القرن الثالث إلى السابع الهجريين : دراسة تحليلية ونقدية في ضوء الكتاب والسنة - الزبون، أحمد محمد عقلة (جامعة آل البيت, 2016)
هدفت هذه الدراسة إلى التعرف إلى آداب الشيخ والمريد الواردة في الرسائل والمؤلفات الصوفية كرسائل الإمام أبو قاسم الجنيد، والغزالي، وابن عربي. وقد حاولت الدراسة الإجابة عن الأسئلة الآتية: - ما الإيجابيات المتعلقة بآداب الشيخ والمريد الواردة في المؤلفات والرسائل الصوفية، في الفترة الزمنية الممتدة من القرن الثالث إلى السابع الهجريين؟ - ما السلبيات المتعلقة بآداب الشيخ والمريد الواردة في المؤلفات والرسائل الصوفية، في الفترة الزمنية الممتدة من القرن الثالث إلى السابع الهجريين؟ استخدمت الدراسة المنهج الوصفي التحليلي للآراء التربوية الواردة في المؤلفات والرسائل الصوفية، واستنباط أهم الإيجابيات والسلبيات المتعلقة بآداب الشيخ والمريد الواردة فيها، وأشارت نتائج الدراسة إلى ما يلي: أولا: تضمنت المؤلفات والرسائل الصوفية، عدة آداب إيجابية تحلى بها الشيخ الصوفي مثل: الأهلية للدعوة والإرشاد، والإذن بالمشيخة والرفق بالمريدين والتواضع لهم، والخبرة بعلم الرياضة الروحية، وأن يكون الشيخ ذا بصيرة وذكاء يمكناه من معرفة صلاحية المريد لسلوك الطريق الصوف، ومخالفة سياسة نفسه، وموافقة قوله لعمله، والعلم بكتاب الله وسنة نبيه صلى الله عليه وسلم، ومعرفة خواطر النفس، واتخاذ مجلس للعلم. ثانيا: اشتملت المؤلفات والرسائل الصوفية على جملة من الآداب الإيجابية تحلى بها المريدون أهمها: احترام المريد لشيخه، والتقوى وأداء ما افترضه الله من فروض وعبادات، والتوبة ورد المظالم، والصدق، وتصحيح العقيدة، وتعلم علوم الشريعة. ثالثا: كشفت الدراسة عن عدة سلبيات تتعلق بآداب كل من الشيوخ والمريدين الصوفيين مثل: وجوب اتخاذ الشيخ وعدم قبول العلم إلا من جهته، والمبالغة في طاعة الشيخ وعدم مخالفته في كل ما يأمر به، تقديم الذكر في الأهمية على كثير من العبادات كقراءة القرآن الكريم، والتوبة المشروطة بعدم نسان الذنب ودوام تذكره، وهجران القرآن الكريم، واتخاذهم ألقاب ومسميات لم ترد في الكتاب والسنة النبوية. وتوصي الدراسة القائمين على عملية تصميم المناهج التعليمية وتطويرها في كافة البلدان الإسلامية بضرورة تضمينها بالآداب الإيجابية المتعلقة بالشيوخ والمريدين والمعلمين والمتعلمين في الفكر التربوي الإسلامي، لتنظيم علاقتهم مع معلميهم على وفق المنهج التربوي الإسلامي القويم.
The study aimed to identify the morals of Al Sheikh and Al mureed mentioned in the Sofia letters and writings, such as the letters of Al Imam Abu AL Qasim ALJunaid, ALGhazali and Ibin Arabi. The study answered the following questions. What are the positive sides related to AL Sheik's and AL mureed's morals mentioned in the sofia letters and writing in third to the seventh centuries hijri? what are the negative sides related to AL Sheik's and AL Mureed's morals mentioned in the sofia letters and writings in the third to the seventh centuries hijri? The descriptive and analytical methods were used in the study for the educational options mentioned in the sofiah letters and evritings by which the positive and negative sides related to AL Sheik’s and AL Mureed's morals, were concluded. The findings showed the mentioned Following: The Sofia writings and letters included lots of positive morals characterized by the sofiah sheikh, such as being qualified for guiding and calling for God, taking permission from the old sheikhs, being kind and humble to AL Muredeen, having good knowledge of spiritual sport, being very smart and having clear vision as sheikh to realize the validity of the Mureed to go on sofiah way by being able to deal correctly with holy Quran and Hadeeth shareef (sunna) and to be among those religious. The Sofia writings and letters included a collection of positive morals the mureedeen have been characterized by , such as respecting the old mureed, being a real believer and worshiping god, honesty, learning the religion and defending the oppressed ones. The study indicated some negative sides related to the morals of, AL Sheik’s and AL Mureedeen in sofiah, such as having the knowledge exclusively from the sheikh exaggerating in obeying the sheikh and never violating his orders, considering repeating religions holy Quran verses more important than worshiping God, to repent but still remembering the guilt, leaving Holy Quran, having nicknames not mention in Holy Quran and Prophet (BUH) Sunna. The study recommended the curriculum designers and developers in all Islamic countries to include the positive morals related to the sheiks, mureedeen, Teachers and learners in the Islamic educational thought in the curricula in order to organize their relation with their teachers according to the right Islamic educational method.
Keywords: التصوف الإسلامى -- الطرق الصوفية -- أخلاقيات المتصوفون -- المؤلفات والرسائل الصوفية